2022
DOI: 10.1007/s00366-021-01568-4
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven approach for linear and nonlinear damage detection using variational mode decomposition and GARCH model

Abstract: In this article, an original data-driven approach is proposed to detect both linear and nonlinear damages in structures using output-only responses. The method deploys variational mode decomposition (VMD) and generalized autoregressive conditional heteroscedasticity (GARCH) model for signal processing and feature extraction. To this end, VMD decomposes the responsesignals are first decomposed to intrinsic mode functions (IMFs), and then, GARCH model is utilized to represent the statistics of IMFs. The model co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…There is a wealth of well-established methods in the ML literature that can effectively decrease feature size, thereby relaxing computational complexity and reducing feature redundancy. Common methods include dimensionality reduction [414], [414]- [421] and feature ranking and selection [8], [125], [414], [422]- [434]. In DL-based feature extraction methods, the substantial size of the resultant deep-learned features necessitates dimensionality reduction since these features constitute a multi-dimensional latent space.…”
Section: Computational Complexitymentioning
confidence: 99%
“…There is a wealth of well-established methods in the ML literature that can effectively decrease feature size, thereby relaxing computational complexity and reducing feature redundancy. Common methods include dimensionality reduction [414], [414]- [421] and feature ranking and selection [8], [125], [414], [422]- [434]. In DL-based feature extraction methods, the substantial size of the resultant deep-learned features necessitates dimensionality reduction since these features constitute a multi-dimensional latent space.…”
Section: Computational Complexitymentioning
confidence: 99%
“…Dragomiretskity et al [18] introduced an adaptive signal analysis approach named VMD that deals with signal processing by formulating and resolving variational issues, providing strong resistance to noise. Owing to its ability to tackle modal mixing and endpoint effect effectively, VMD finds applications in multiple fields, including generator anomaly detection, structural health monitoring, and bearing fault diagnosis [19][20][21]. Li and colleagues [22] devised a diagnosis method for fault detection in rolling bearings using VMD and improved Kernel Extreme Learning Machine and demonstrated that VMD successfully addressed the mode mixing problem and boasted superior computational efficiency compared to EMD and LMD methods.…”
Section: Introductionmentioning
confidence: 99%